Perbandingan Pengaruh Dosis Kombinasi Ultrasound dan McKenzie terhadap Nyeri, Fleksibilitas, dan Kemampuan Fungsional pada Pasien Nyeri Punggung Bawah - Arief Efendi; Nurul Halimah; Afrizal Febri Eko Saputra; Aril Firzan Syahroni (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
Background: Low back pain (LBP) is a common musculoskeletal disorder associated with reduced lumbar flexibility and functional ability. Ultrasound and McKenzie exercise are commonly combined in physiotherapy; however, the optimal exercise dosage remains unclear. Objective: This study compared the effects of two dosages of combined ultrasound and McKenzie exercise (10 repetitions × 2 sets and 10 repetitions × 3 sets) on pain, flexibility, and functional ability in patients with LBP. Methods: A quasi-experimental pretest-posttest two-group design was conducted involving 40 patients with LBP aged 25–60 years and symptom duration of 4–24 months. Participants were divided into Group A (2 sets; n = 20) and Group B (3 sets; n = 20). Pain was assessed using the Visual Analogue Scale (VAS), lumbar flexibility using the Modified Schober Test (MST), and functional ability using the Oswestry Disability Index (ODI). Data were analysed using paired-samples and independent-samples t-tests at α = 0.05. Results: Both groups demonstrated significant improvements in VAS, MST, and ODI scores (p < 0.001). Group B achieved greater improvements than Group A in delta VAS (3.08 ± 0.44 vs. 2.15 ± 0.40), delta MST (1.41 ± 0.31 vs. 0.86 ± 0.27), and delta ODI (18.20 ± 4.25 vs. 12.40 ± 3.02), with p < 0.001 for all outcomes. Conclusion: Combining ultrasound with McKenzie exercise at 10 repetitions × 3 sets produced greater reductions in pain and greater improvements in lumbar flexibility and functional ability than the 2-set dosage in patients with LBP.